Inventory level change before and after the great east Japan earthquake: implications for just-in-time / Shinnosuke Hara - Hara, Shinnosuke (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
Just-in-time (JIT) is an excellent Japanese management technique. However, it has received criticisms about its limitation during unexpected disasters, especially after the Great East Japan Earthquake. Some companies prefer to stock as a countermeasure to the damage sustained by supply chains. Though the earthquake had a significant effect, is such a decision appropriate? How did Toyota Motor Corporation (the originator of JIT) behave in this situation? In this study, we address these question through an investigation of the inventory turnover of Toyota and its suppliers. We analyze the inventory turnover using statistical tests. Our results support the tendency of companies to increase inventory possession after an earthquake. However, a particular company showed a tendency to decrease its inventory. Considering the situation of all the suppliers when evaluating inventory control is necessary because the analysis is conducted at the supply chain level.